Characterization of Metagenomes in Urban Aquatic Compartments Reveals High Prevalence of Clinically Relevant Antibiotic Resistance Genes in Wastewaters - Ng, Charmaine; Tay, Martin; Tan, Boonfei; Le, Thai-Hoang; Haller, Laurence; Chen, Hongjie; Koh, Tse H.; Barkham, Timothy M. S.; Thompson, Janelle R.; Gin, Karina Y.-H. (Frontiers in Microbiology, 2017)
The dissemination of antimicrobial resistance is an escalating problem and a threat to public health. Comparative metagenomics was used to investigate the occurrence of antibiotic resistant genes (ARGs) in wastewater and urban surface water environments in Singapore. Hospital and municipal wastewater (n=6) were found to have higher diversity and average abundance of ARGs (303 ARG subtypes, 197,816 x/Gb) compared to treated wastewater effluent (n=2, 58 ARG subtypes, 2,692 x/Gb) and surface water (n=5, 35 subtypes, 7,985 x/Gb). A cluster analysis showed that the taxonomic composition of wastewaters was highly similar and had a bacterial community composition enriched in gut bacteria (Bacteroides, Faecalibacterium, Bifidobacterium, Blautia, Roseburia, Ruminococcus), the Enterobacteriaceae group (Klebsiella, Aeromons, Enterobacter) and opportunistic pathogens (Prevotella, Comamonas, Neisseria). Wastewater, treated effluents and surface waters had a shared resistome of 21 ARGs encoding multidrug resistant efflux pumps or resistance to aminoglycoside, macrolide-lincosamide-streptogramins (MLS), quinolones, sulfonamide and tetracycline resistance which suggests that these genes are wide spread across different environments. Wastewater had a distinctively higher average abundance of clinically relevant, class A beta-lactamase resistant genes (i.e. blaKPC, blaCTX-M, blaSHV, blaTEM). The wastewaters from clinical isolation wards, in particular, had exceedingly high levels of blaKPC-2 genes (142,200 x/Gb), encoding for carbapenem resistance. Assembled scaffolds (16 and 30 kbp) from isolation ward wastewater samples indicated this gene was located on a Tn3-based transposon (Tn4401), a mobilization element found in Klebsiella pneumonia plasmids. In the longer scaffold, transposable elements were flanked by a toxin-antitoxin (TA) system and other metal resistant genes that likely increase the persistence, fitness and propagation of the plasmid in the bacterial host under conditions of stress. A few bacterial species (Enterobacter cloacae, K. pneumoniae, Citrobacter freundii, Pseudomonas aeruginosa) that were cultured from the isolation ward wastewaters on CHROMagar media harbored the blaKPC-2 gene. This suggests that hospital wastewaters derived from clinical specialty wards are hotspots for the spread of antimicrobial resistance. Assembled scaffolds of other mobile genetic elements such as IncQ and IncF plasmids bearing quinolone resistance genes (qnrS1, qnrS2) and the class A beta-lactamase gene (blaTEM-1) were recovered in wastewater samples which may aid the transfer of antimicrobial resistance.